2020
DOI: 10.5539/ijel.v10n2p322
|View full text |Cite
|
Sign up to set email alerts
|

Genre Analysis of Civil Engineering’s Research Article Introductions

Abstract: The present study explores the structures of Civil Engineering research articles’ (RA) introductions based on Swales’ 1990 CARS (Create a Research Space) model. It analyzes fifteen Civil Engineering research articles’ introductions according to the move structure and linguistic features that would indicate the use and avoidance of the move. Findings show that move-pattern in RA introductions of this field follow all three moves but it does not adhere to the proposed sequence given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Swales' (1990) [11] move analysis focuses on the IMRD framework (Introduction, Method, Result and Discussion), and Bhatia (1993) [10] divided the moves into four different categories: introduction purpose, description of methodology, summary of results, and presentation of conclusions. Ngowu (1997) [13], [26] analyzed structures of civil engineering research articles' introduction and concluded that the introduction genre in the field does not have the proposed sequence given in the model. In another study, [27] analyzed engineering research articles to address the need for discipline-specific writing for beginners of the English language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Swales' (1990) [11] move analysis focuses on the IMRD framework (Introduction, Method, Result and Discussion), and Bhatia (1993) [10] divided the moves into four different categories: introduction purpose, description of methodology, summary of results, and presentation of conclusions. Ngowu (1997) [13], [26] analyzed structures of civil engineering research articles' introduction and concluded that the introduction genre in the field does not have the proposed sequence given in the model. In another study, [27] analyzed engineering research articles to address the need for discipline-specific writing for beginners of the English language.…”
Section: Literature Reviewmentioning
confidence: 99%